2007
DOI: 10.1016/j.drugalcdep.2006.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Regardless of psychiatric severity the addition of contingency management to standard treatment improves retention and drug use outcomes

Abstract: The relationship between psychiatric severity and substance use disorders treatment outcome was assessed in 393 individuals who received either standard treatment or standard treatment plus contingency management. The sample was divided into groups of low, moderate, and high psychiatric severity based upon baseline Addiction Severity Index psychiatric composite scores. Participants in the high psychiatric severity group reported a greater prevalence of psychiatric hospitalization, psychiatric medications, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Furthermore, in contrast to the common finding that treatment outcomes for substance abuse and dependence are diminished among those with greater severity of psychiatric symptoms and among those with concomitant psychiatric disorders (Charney, Palacios-Boix, Negrete, Dobkin, & Gill, 2005; Compton, Cottler, Jacobs, Ben-Abdallah, & Spitznagel, 2003), CM is associated with greater reductions in substance use and increased retention rates in participants with high psychiatric severity compared to standard treatment (Weinstock, Alessi, & Petry, 2007). CM has also demonstrated efficacy compared to standard substance abuse treatments in producing abstinence among drug abusers with comorbid psychiatric condition(s) (Drake, O’Neal, & Wallach, 2008), with particularly strong findings for cocaine- and opioid-dependent individuals with post-traumatic stress disorder (Mancino et al, 2010) cocaine abusers with antisocial personality disorder (Messina et al, 2003), and substance-dependent, homeless MSM with antisocial personality disorder (Fletcher & Reback 2013).…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, in contrast to the common finding that treatment outcomes for substance abuse and dependence are diminished among those with greater severity of psychiatric symptoms and among those with concomitant psychiatric disorders (Charney, Palacios-Boix, Negrete, Dobkin, & Gill, 2005; Compton, Cottler, Jacobs, Ben-Abdallah, & Spitznagel, 2003), CM is associated with greater reductions in substance use and increased retention rates in participants with high psychiatric severity compared to standard treatment (Weinstock, Alessi, & Petry, 2007). CM has also demonstrated efficacy compared to standard substance abuse treatments in producing abstinence among drug abusers with comorbid psychiatric condition(s) (Drake, O’Neal, & Wallach, 2008), with particularly strong findings for cocaine- and opioid-dependent individuals with post-traumatic stress disorder (Mancino et al, 2010) cocaine abusers with antisocial personality disorder (Messina et al, 2003), and substance-dependent, homeless MSM with antisocial personality disorder (Fletcher & Reback 2013).…”
Section: Introductionmentioning
confidence: 79%
“…For example, symptoms of social anxiety may trigger drinking alcohol due to its ability to reduce uncomfortable feelings (Battista et al, 2015). Unfortunately, psychiatric comorbidity within SUD is frequently associated with greater impairment and poor treatment engagement (Greenfield et al, 1998; Weinstock, Alessi, & Petry, 2007), both of which can lead to poor treatment outcome and relapse to substance use. Conversely, exercise is an effective treatment for both major depression and certain anxiety disorders (e.g., Babyak et al, 2000; Broocks et al, 1998), which are disorders that frequently co-occur with SUD (Grant et al, 2004).…”
Section: 2 Rationale For Exercisementioning
confidence: 99%
“…Results suggest that CM is efficacious and generalizable to a wide range of characteristics including income (Rash, Andrade, & Petry, 2013; Rash, Olmstead, & Petry, 2009; Secades-Villa et al, 2013), race (Barry, Sullivan, & Petry, 2009), gender (Burch, Rash, & Petry, 2015; Rash & Petry, 2015), comorbid disorders (Ford, Hawke, Alessi, Ledgerwood, & Petry, 2007; GarcĂ­a-Fernández, Secades-Villa, GarcĂ­a-RodrĂ­guez, Peña-Suárez, & Sánchez-Hervás, 2013; Rash, Alessi, & Petry, 2008a; Weinstock, Alessi, & Petry, 2007), co-occurring substance use (Alessi, Rash, & Petry, 2011), medical comorbidities (Burch, Morasco, & Petry, 2015; Walter & Petry, 2015), history of prior SUD treatment (Rash, Alessi, & Petry, 2008b), and history of prostitution (Rash, Burki, Montezuma-Rusca, & Petry, 2016). In this issue, Shoptaw and colleagues (2017) have shown that abstinence-based incentives can be effective even outside the context of formal SUD treatment with MSM (men who have sex with men) methamphetamine users enrolled in an HIV risk reduction project.…”
Section: For Whom Is CM Effective?mentioning
confidence: 99%